Ophthalmological Metabolic Diseases and Stem Cells - Gazcón, Héctor Zúñiga-; elgado, Miguel Angel Flores D; Mayorga, Diego Eduardo Saavedra; Calderon, Luis Antonio Villalobos; Ramírez, María Holanda García (International Journal of Medical Science and Clinical Research Studies, 2022)
Ocular pathologies are, without a doubt, one of the most complicated at the time of regulating medical therapy. Being one of the most relevant sense organs (if not the most important) the use of stem cells in the treatment of metabolic diseases that were previously considered to be slow-progressing, significant improvement can now be achieved.